Numerical modeling of growth of multiplicative random quantities - Grachev, D.A.; Sokoloff, D.D. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2006)
We present some results of numerical modeling for a simple ordinary differential equation with a random coefficient. We compare these results with the previous results obtained when modeling the Jacobi fields on a geodesic line on a manifold with a random curvature. We demonstrate a subexponential growth for the solution, while the solutions to the Jacobi equation grow exponentially. A progressive growth of statistical moments is demonstrated. The sample size sufficient for such a progressive growth is shown to be as large as 10^3, while the size required for the Jacobi equation is about 10^5.